Managing IT skills portfolios planning, acquisition, and performance evaluation - Nakayama, Makoto; Sutcliffe, Norma; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
"This book provides the basic vocabulary and managerial framework for managing strategically the IT workforce at the firm level. It also informs managers what tools and services are available to assess the skill levels of their IT workforce and job candidates. Finally, it gives different perspectives on managing IT skills; how individuals, HR managers, educators, and governments approach IT skills management"--Provided by publisher.
1. Skills, management of skills, and IT skills requirements / Makoto Nakayama, Norma Sutcliffe -- 2. An approach for managing IT skills portfolio / Makoto Nakayama, Norma Sutcliffe -- 3. Challenges for managing IT skills portfolio for e-business / Abdulrahman Mirza, Susy Chan -- 4. Skills and the worker / Elizabeth Lahey -- 5. Optimizing IT skills management initiatives / Ken Strauss -- 6. Government involvement in skills issues / Elizabeth Lahey -- 7. Japanese IT-skill dilemma / Yoko Takeda -- 8. Eliminating the weakest link / Diana Wong-Ming Ji -- 9. An Exploration of the value of Information systems certification / John Anderson, Kevin Barrett, Paul Schwager -- 10. Extreme interviewing to find team oriented programmers / Clement Boebel, Richard Sheridan, Thomas Meloche.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 6, 2010).
Keywords: Information resources management; Information technology -- Management; Electronic books